Plato's ghost : the modernist transformation of mathematics - Gray, Jeremy, 1947- (Princeton University Press, 2008)
Plato's Ghost examines the development of mathematics from 1880 to 1920 as a modernist transformation similar to those in art, literature, and music. --from publisher description.